THE ROLE OF DIFFUSE OPTICAL SPECTROSCOPY IN THE DIAGNOSIS OF BREAST CANCER (CASE REPORT) - M. V. Pavlov; S. A. Pegov; A. G. Orlova; G. Yu. Golubyatnikov; L. V. Shkalova; P. A. Malinina; P. I. Rykhtik; I. V. Turchin; A. V. Maslennikova (Сибирский онкологический журнал)
Breast cancer (BC) is one of the most common malignancies and the leading cause of cancer-related death in women worldwide. Currently, mammography and ultrasound are the methods most commonly used for the detection of BC, but these methods have significant limitations in the absence of “classic” visual symptoms of cancer in the breast tissue. In the complicated clinical situations, such methods as magnetic resonance imaging and positron emission tomography are used for the differential diagnosis of breast cancer. Over the past 20 years, the BC imaging capabilities have expanded due to the introduction of optical methods into clinical practice. These methods are based on differences in the optical properties between normal and pathological breast tissues. Optical imaging provides the ability to obtain indirect information about oxygenation, blood supply, delivery and consumption of oxygen in the breast tissue, as well as changes in its scattering properties. We present a clinical case of a woman with enlarged axillary lymph nodes. After the core biopsy of the lymph node, histological examination reveled breast cancer metastasis. The standard imaging modalities, such as digital mammography and ultrasound, did not show the evidence of breast cancer. However, the use of diffuse optical spectroscopy (DOS) allowed the detection of changes in the absorption and scattering coefficients in a small part of the breast tissue characteristic of a malignant tumor. Ultrasound and mammography images of this site of the breast demonstrated the features of benign lesion. After ultrasound-guided biopsy, cytological examination revealed cancer cells. Thus, the method of DOS allowed identification of changes characteristic to malignant tumor that was not detected by routine imaging modalities.